Enzyme Replacement Therapy may Affect Blood Immunosuppressant Monitoring - Gönel, Ataman; Koyuncu, Ismail; Bayraktar, Nihayet; Tayman, Cüneyt; Bardakçı, Osman; Uzunköy, Ali; Guzelcicek, Ahmet (Current Pediatric Reviews, 2020)
Background: Although LC-MS/MS is preferred as a reliable method, therapeutic enzyme drugs in the blood matrix may lead to false results. Objective: The purpose of this article is to experimentally investigate the effect of five different enzymes used in the treatment of metabolic diseases on blood immunosuppressant measurement. Methods: Five different enzyme drugs (galsulfase, alglucosidase alfa, imiglucerase, elosulfase alfa, laronidase) were added to control materials containing tacrolimus, everolimus, sirolimus, and cyclosporine A drugs. Measurements were performed using an LC-MS/MS instrument (Shimadzu 8040, Japan). The amount of deviations from the target values was calculated. Results: Blood Immunosuppressant levels significantly changed after the administration of enzyme drugs. Four different enzyme drugs led to false-positive results in the tacrolimus levels at a rate of 10.58% (95% CI, 9.83-11.32) to 37.28% (95% CI, 33.55-41.27). The highest deviations were observed with the administration of galsulfase and alglucosidase alpha in the sirolimus levels at rates of 336.54% (95% CI, 306.25-366.82) and 395.88% (95% CI, 360.25-431.50), respectively. Imiglucerase was the least effective enzyme for the sirolimus level (0.80% (95% CI, 0.71-0.89). Different deviations between the ratios of - 9.37% (95% CI, -10.40 - -8.33) and 8.33% (95% CI, 7.41-9.24) were determined at the cyclosporin A level. Conclusion: Galsulfase, alglucosidase alpha, imigluserase, elosulfase alpha and laronidase can significantly interfere with immunosuppressant measurements with LC-MS/MS. False immunosuppressant results associated with enzyme injection may result in immunosuppression failure, organ rejection. For the measurement of immunosuppressant levels, sampling should be done before the enzyme infusion. Clinicians should question the time of enzyme infusion and sampling when confounding results in immunosuppressant measurement.
Keywords: matrix effect